Research Activities in the Teaching Intensive University: Scholarship Reconsidered & Repositioned (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2018)
A quarter of a century has passed since Professor Ernest L. Boyer's landmark book, Scholarship Reconsidered: Priorities of the Professoriate, challenged the publish-or-perish status quo that dominated the academic landscape then and has continued to do so through a variety of research league-table games. His powerful and enduring argument for a broader approach to academic roles and rewards within universities continues to be important as higher education providers balance the varying expectations of their role in society. This paper is more an examination of the provenance of the Boyer model than a review of the book.